2021
DOI: 10.5811/westjem.2021.4.50476
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Social Determinants of Health in an Urban Emergency Department

Abstract: Introduction: Social determinants of health (SDOH) have significant impacts on patients who seek care in the emergency department (ED). We administered a social needs screening tool and needs assessment survey to assess SDOH and evaluate for trends in the population of patients visiting our ED. Methods: A survey was distributed via convenience sampling to adult ED patients to capture self-reported demographic information and data about social needs. We categorized the questions related to SDOH based on the In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Texas did not expand Medicaid coverage under the Affordable Care Act, and most patients in this health system are underinsured or use a county financial assistance program (FAP) for medical services within the hospital system. 31 , 32 This study received institutional review board approval.…”
Section: Methodsmentioning
confidence: 99%
“…Texas did not expand Medicaid coverage under the Affordable Care Act, and most patients in this health system are underinsured or use a county financial assistance program (FAP) for medical services within the hospital system. 31 , 32 This study received institutional review board approval.…”
Section: Methodsmentioning
confidence: 99%
“…Second, although personality traits are not typically assessed in healthcare settings currently, there is a precedent for doing so given that other personality-related questions are often asked in routine care settings as screeners (e.g., "to what extent have you felt sad lately" as a screener for depression) and recent research has begun to examine the utility of assessing social determinants of health in healthcare settings (e.g., Ordonez et al, 2021). Incorporating personality assessment into healthcare systems in an efficient manner would be necessary before direct healthcare applications are possible.…”
Section: Implications For Healthcare Delivery and Policymentioning
confidence: 99%
“…9 More importantly, overall vaccine hesitancy observed in the general population has been linked to the level of hesitancy among HCWs in general. 10 To date, only two studies have explicitly addressed COVID-19 vaccine hesitancy and immunization rates of EMS personnel. In a cross-sectional survey of US firefighters and EMS personnel, Caban-Martinez et al reported that over half of their respondents were either uncertain or unlikely to receive the vaccine.…”
Section: Introductionmentioning
confidence: 99%